PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE ROTATING TRIO EXCHANGE (RTE) UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN IKATAN KIMIA DI KELAS X MIA SMA NEGERI 1 BANGKINANG KOTA - ', Hasnah; ', Herdini; ', Miharty (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The research about application of cooperative learning model Rotating Trio Exchange (RTE) has been done to improve student achievement on the subject of chemical bonds in ten Science class senior high school city Bangkinang. The research is from of experimental research with pretest-posttest design. samples consist of two classes; ten Science one class as the experimental class and ten Science two class as the control class of randomly chosen after the normality test and homogeneity test. Experimental class is a class that treated by applying model Rotating Trio Exchange (RTE), while the control class without applying model Rotating Trio Exchange (RTE). Data analysis technique used the t-test. Based on the final results of data process by using t-test formula obtained ttest>ttabel is 1,92>1,67 means that the applications of cooperative learning model Rotating Trio Exchange (RTE) can improve student achievement on the subject of chemical bonds in class X Science senior high school city Bangkinang with effect 5,45%.Keywords : Cooperative learning model Rotating Trio Exchange (RTE), Learning Achievement , And Chemical Bonds